PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN, DAN SOLVABILITAS TERHADAP AUDIT REPORT LAG DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA - Nurvilawati, Viananda; Yudea, Yudea; Karlinda Sari, Dika (Jurnal GeoEkonomi, 2024)
The Influence of Company Size, Company Age, and Solvency on Audit Report Lag Profitability Using Moderating Variables in Mining Sector Companies on the Indonesian Stock Exchange for the 2020-2022 Period. Supervisors: Mr. Judea and Mrs. Dika Karlinda Sari. This research aims to determine the influence of company size, company age and solvency on audit report lag profitability using moderating variables in mining sector companies on the Indonesian Stock Exchange for the 2020-2022 period. The total sample tested was 19 companies selected using purposive sampling technique. The data analysis techniques used are multiple linear regression, Moderated Regression Analysis dan hypothesis testing. Based on the results of the analysis, it shows that company size, company age, and solvency simultaneously have no effect on audit report lag. Partially, company size, company age, and solvency simultaneously have no effect on audit report lag. In Moderated Regression Analysis, profitability is not able to moderate company size, company age, solvency and audit report lag.